CURRENT EMPLOYABILITY SCENARIO OF INDIAN GRADUATES SCENARIO OF INDIAN MBA GRADUATES: A REVIEW - Harshitha K S (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2020)
The purpose of this theoretical article is to address some issues of employability skills required by MBA Graduates and to give some suggestions for improving their skills to make themselves 'Employable'. This paper reviews drawbacks in existing Higher Education system and how it makes students only Degree based and not Skilled based job seeker which makes them incapable for getting job employment. Paper also discusses some serious problems and challenges currently facing by today's youth regarding skills and jobs. In today's scenario, because of Globalization, Advancement in Technology industries are facing a tough competition in keeping and maintaining their existence and share in the market for which they immensely require a pool of candidate which are having high level of skills in order to meet changing market needs and wants . But as the time changes, market witnessed a radical shift in economic activities. Due to advancement in technology, nature of jobs, businesses , employment have been transformed. In today's era, staying updated with technological advancements and rapid changes in surrounding are of prime importance for both success and growth of Individual and Business. = With each passing day, gap between actual skills and required skills by the market are widening and in order to fill this gap, companies are also adopting newer modes of recruitment to acquire the 'Skilled' Talents. And for attracting "Best Skilled talents" employers are focusing on Employer branding, Referrals , Data driven-recruiting using social media channels etc. Employers all around the world are prominently looking for hiring the best talents. But still the gap between academic knowledge and the skills which are required professionally is widening because the lack of necessary skills which are required to meet the growing demands. Experts believe that this gap exists because many students though they have strong faith in their abilities, but very few people are able to make their passion as their career choice. the But because of family pressure, friend circles or some other reasons they don't want to take huge risk which occur while making life changing decisions about their career. Now-a days, it is very important for youth people to remain synchronized with the latest current trends and developments in the market. Also they need to upgrade their skills in order to create demand for themselves not just in India but globally.